Evaluation of different zinc sources and levels on nursery pig performance - Jordan, Kyle E.; Goncalves, Marcio Antonio Dornelles; Nitikanchana, Sureemas; Tokach, Michael D.; Dritz, Steven S.; Goodband, Robert D.; DeRouchey, Joel M.; Woodworth, Jason C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
A total of 294 pigs (PIC 327 × 1050, initially 14.1 lb BW) were used in a 31-d trial to evaluate the effects of increasing levels of two different zinc sources on nursery pig growth performance. Pigs were weaned at 21 d of age and were fed pelleted diets for the first 7 d and a mash diet for 24 d of the 31-d trial. Each treatment had 7 replicate pens with 7 pigs per pen. The 6 experimental diets were: (1) a control diet; (2) a diet with 500 ppm of Zn from Zinco+; (3) a diet with 1,500 ppm of added Zn from Zinco+; (4) a diet with 500 ppm of Zn from zinc oxide (ZnO); (5) a diet with 1,500 ppm of Zn from ZnO; and (6) a diet with 3,000 ppm of Zn from ZnO. All diets contained 110 ppm of Zn from the ZnSO4 provided by the trace mineral premix. Zinco+ (Jefo, Quebec, Canada) is a fat-encapsulated form of ZnO that is suggested to be more bioavailable than ZnO. From d 0 to 7, neither Zn source nor level influenced pig performance. From d 7 to 21, pigs fed increasing Zn from Zinco+ tended to have increased (linear, P = 0.06) ADG and had improved F/G (linear, P < 0.01). Pigs fed increasing levels of Zn from ZnO had greater ADG and ADFI (linear, P < 0.01) and improved F/G (quadratic, P = 0.02). Pigs had greater (P < 0.01) ADG and ADFI when fed diets containing 3,000 ppm of Zn from ZnO compared with pigs fed diets with 500 ppm of Zn from Zinco+. Day 21 BW increased with increasing Zn from Zinco+ (linear, P < 0.03) and Zn from ZnO (P < 0.001), with pigs fed 3,000 ppm of Zn from ZnO having heavier (P < 0.01) d-21 BW compared with those fed 500 ppm of Zn from Zinco+. Overall, from d 0 to 31, increasing Zn from Zinco+ did not affect growth performance, but increasing Zn from ZnO increased (P < 0.01) ADG and ADFI. Pigs fed 500 ppm of Zn from Zinco+ had poorer ADG (P < 0.02) and ADFI (P < 0.01) than pigs fed 3,000 ppm of Zn from ZnO. This study shows the growth benefits of adding 3,000 ppm of Zn from ZnO in diets fed to newly weaned pigs. Lower levels of Zn from Zinco+ did not provide the same growth-promoting potential as the diet with 3,000 ppm of Zn from ZnO.
Swine Industry Day, 2014 is known as Swine Day, 2014
Keywords: Growth performance; Nursery pig; Zinc